2020
DOI: 10.1186/s12893-020-00907-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between postoperative changes in the gut microbiota and pseudopsia after cardiac surgery: prospective observational study

Abstract: Background Delirium after cardiac surgery affects mortality, but the mechanism remains unclear. Previous studies have reported gut microbiota are associated with brain activity. Systemic inflammation and antibiotics can damage the gut microbiota after cardiac surgery. We aimed to investigate changes in the gut microbiota and the association between the gut microbiota and delirium after cardiac surgery. Methods Twenty-one patients who… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The anti-inflammatory mechanism entails direct interaction with immune cells to block histone deacetylases, resulting in more transcriptionally active chromatin and down-regulated inflammatory cytokines, such as TNF-a and IL-12 35. In addition, SCFAs were reported to be directly associated with memory function recovery and an increase in gene expression involved associative learning 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory mechanism entails direct interaction with immune cells to block histone deacetylases, resulting in more transcriptionally active chromatin and down-regulated inflammatory cytokines, such as TNF-a and IL-12 35. In addition, SCFAs were reported to be directly associated with memory function recovery and an increase in gene expression involved associative learning 31…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, SCFAs were reported to be directly associated with memory function recovery and an increase in gene expression involved associative learning. 31 By applying elevations of plasma TJ protein and endotoxin as markers of gut barrier dysfunction, researchers observed increased intestinal permeability after surgery. 36 In our study, plasma LPS, claudin-1, and occludin were higher in pAD patients prior to surgery, particularly in SCD patients, which may suggest preexisting high intestinal permeability in pAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study of the relationship between the gut microbiota and pseudopsia after cardiac surgery, Maekawa et al ( 22 ) reported that surgery lowered the total bacterial counts and species numbers. Staphylococcus and Pseudomonas counts were significantly higher postoperatively, and may be associated with the pathogenesis of pseudopsia.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of POD, Zhang et al ( 21 ) detected an association between an abnormal composition of the gut microbiota and delirium-like behaviors after abdominal surgery in mice. Additionally, Maekawa et al ( 22 ) observed a clinical association between pseudopsia and the gut microbiota among patients who underwent cardiac surgery. However, the relationship between POD and the gut microbiota in various surgery types and the relationship with aging has not been widely examined.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular active drugs such as isoprotereno were used if HR < 50 bmp (anticholinergic drugs were avoided). Cefazolin was used 30–60 min before surgery to prevent infection ( Maekawa et al, 2020 ). Cefazolin was added every 3 h or when the bleeding volume was greater than 1,000 ml.…”
Section: Methodsmentioning
confidence: 99%